Factors related to mouth-breathing syndrome and the influence of an incompetent lip seal on facial soft tissue form in children. Issue 1 (April 2021) - Inada, Emi; Saitoh, Issei; Kaihara, Yasutaka; Yamasaki, Youichi
Abstract: Background: Mouth breathing syndrome (MBS) is defined as a set of signs and symptoms that may be completely or incompletely present in subjects who, for various reasons, replace the correct pattern of nasal breathing with an oral or mixed pattern. Better understanding of the characteristics of MBS at each stage of growth will be helpful for the accurate diagnosis and treatment of MBS. Objective: This review aimed to clarify the relevant factors affecting MBS in children and to examine the influence of an incompetent lip seal (ILS) on facial soft tissue form in preschool-aged children. Results: Recent data have shown that an ILS affects MBS in children. In addition, the factors associated with MBS in preschool-aged children were not mutually unrelated, and multiple factors such as general conditions, lifestyle, and eating habits may interact with one another. Furthermore, children with an ILS already tended to have a flattened nose and an anteriorly prominent lip at 3 years of age, implying that the adverse effects of an ILS on the growth of the craniofacial region appear relatively early. Conclusions: These results suggest the importance of early diagnosis and treatment of MBS. Early treatment of MBS may prevent possible dental and physical problems in the future.